Fallstudie: en analys av Kungens Kurva utifrån Huddinge kommuns vision för vidare utveckling av området - Lennfalk, Fredrik (2011)
In this thesis, a case study of Kungens Kurva in Stockholm is made. The municipality of Huddinge has designated the area, which is an external shopping-center, as one of its key development areas in the future. The municipality has established a future vision for the area, which extends until 2030. The vision claims, inter alia, that Kungens Kurva along with Skärholmen will become a vibrant suburb. How well the values and aims of the vision are met in the current area situation is discussed in the case study by a number of analysis that carries out the existing structures and characters of the area. The vision is also discussed from out a view of economic, social and ecological sustainability. The main literature used as a theoretical framework for consisting analysis are Kevin Lynch's “The Image of the City”, Jan Gehl's “Livet Mellem Husene” and Erland Ullstad's “Hållbar stadsutveckling – en politisk handbok från Sveriges Arkitekter”. Analysis of the current area situation, together offers a picture of what changes must be made for the values and aims of the vision to be realized in the future. They reveal, inter alia, that Kungens Kurva must be made more accessible and that the area must include a more mixed character to be able to respond to the vision. Implementation of households in the area is seen as an important future development. A number of barriers, which are particularly detrimental to pedestrian and bicycle road passing, as well as large-scale buildings and exposed parking surfaces, which makes a vibrant city life impossible, are also pointed out as problematic structures and characters in the area. The actual vision is however considered to possess good qualities, and it is noted that many of its parts is pervaded by a view of economic, social and ecological sustainable development. The thesis strengthens many parts of the earlier research that Anna Carlberg has done in the area in her thesis “Centrum i periferin”.